Perancangan Dan Analisis Sistem Single Axis Sun Tracker Untuk Meningkatkan Daya Output Solar Photovoltaic - Ichsan Maulana Putra; Iswadi Hasyim Rosma (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
The use of Solar Photovoltaic (SPV) is widely installed at a specific tilted angle. This condition causes the solar PV panel will not get optimum solar radiation from the sun. Therefore, to overcome this situation, a solar panel based sun tracker was designed and installed. The sun tracker was using two LDR sensors to detect the position of the sun. An ardunio microcontroller was employed as controller system to inquiry the motor servo, in order to drive solar panel toward the sun location. Four different titled angles of solar panel such as 0 °, 15 °, 30 ° and 45 ° were compared with sun tracker based solar panel to obtain the energy gaining. It was found that the sun tracker based solar panel gave a significant energy boost. The energy gaining compare with 0 °, 15 °, 30 ° and 45 ° was 12%, 16%, 20% and 22%, respectively. From the real condition test, it can be concluded that there is a high potential of energy gaining when solar panel is equipped with sun tracker.Keywords: Arduino, Data Logger Shield, LDR, Servo Motor, Solar Photovoltaic